Coulomb effects in isobaric cold fission from reactions 233-U(nth,f), 235-U(nth,f), 239-Pu(nth,f) and 252-Cf(sf) - Montoya, Modesto (2014)
The Coulomb effect hypothesis, formerly used to interpret fluctuations in the curve of maximal total kinetic energy as a function of light fragment mass in reactions 233-U (nth,f), 235-U(nth,f) and 239-Pu(nth,f), is confirmed in high kinetic energy as well as in low excitation energy windows, respectively. Data from reactions 233-U (nth,f), 235-U(nth,f), 239-Pu(nth,f) and 252-Cf(sf) show that, between two isobaric fragmentations with similar Q-values, the more asymmetric charge split reaches the higher value of total kinetic energy. Moreover, in isobaric charge splits with different Q-values, similar preference for asymmetrical fragmentations is observed in low excitation energy Windows.